Age-Related Cancer-Associated Microbiota Potentially Promotes Oral Squamous Cell Cancer Tumorigenesis by Distinct Mechanisms - Zhang, Zhen; Feng, Qiang; Li, Meihui; Li, Zhihui; Xu, Qin; Pan, Xinhua; Chen, Wantao (Frontiers in Microbiology, 2022)
The OSCC incidence in young patients has increased since the end of the last century; however, the underlying mechanism is still unclear. Oral microbiota dysbiosis was proven to be a tumorigenesis factor, and we propose that there is a distinct bacterial composition in young patients that facilitates the progression of OSCC. Twenty elderly (>60 years old) and 20 young (<50 years old) subjects were included in this study. OSCC tissue was collected during surgery, sent for 16S rDNA sequencing and analysed by the QIIME 2 pipeline. The results showed that Ralstonia, Prevotella and Ochrobactrum were significantly enriched in younger OSCC tissue microbiota, while Pedobacter was more abundant in elderly OSCC tissues. Fusobacterium had high relative abundance in both cohorts. At the phylum level, Proteobacteria was the dominant taxon in all samples. The functional study showed that there were significant differences in the taxa abundance from metabolic and signalling pathways. The results indicated that the microbiota of younger OSCC tissues differed from that of elderly OSCC tissues by both taxon composition and function, which partially explains the distinct roles of bacteria during tumorigenesis in these two cohorts. These findings provide insights into different mechanisms of the microbiota-cancer relationship with regard to ageing.